2019
DOI: 10.1108/nfs-04-2018-0113
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant status and risk of coronary artery disease

Abstract: Purpose Coronary artery disease (CAD) is developed by an insufficient supply of oxygen-rich blood to the myocardium. Recent studies have shown that increased oxidative stress has implicated in the pathogenesis of coronary atherosclerosis. Anxiety and CAD have a mutual relationship, as the effect of long-lasting anxiety on atherosclerosis and CAD is well known. The purpose of this study is to investigate the relationship between dietary / serum total antioxidant capacity and CAD. Design/methodology/approach A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…It seems that oxidative stress could play an important role in the pathogenesis of various chronic diseases such as diabetes, obesity, atherosclerosis and autoimmune diseases (Fatahi et al, 2018). In the past years, there is a growing interest in investigating the dietary sources of antioxidants and the role of dietary antioxidants in prevention of diseases (Talebi et al, 2018;Mancini et al, 2018;Yang et al, 2017;Fatahi et al, 2018;Otemuyiwa et al, 2017;Shuvo et al, 2017). Results of our study, for the first time, revealed that foods containing antioxidants could play a preventive role in development of NMOSD.…”
Section: Discussionmentioning
confidence: 53%
“…It seems that oxidative stress could play an important role in the pathogenesis of various chronic diseases such as diabetes, obesity, atherosclerosis and autoimmune diseases (Fatahi et al, 2018). In the past years, there is a growing interest in investigating the dietary sources of antioxidants and the role of dietary antioxidants in prevention of diseases (Talebi et al, 2018;Mancini et al, 2018;Yang et al, 2017;Fatahi et al, 2018;Otemuyiwa et al, 2017;Shuvo et al, 2017). Results of our study, for the first time, revealed that foods containing antioxidants could play a preventive role in development of NMOSD.…”
Section: Discussionmentioning
confidence: 53%
“…Antioxidant enzymes play a critical role against lipid peroxidation processes. Several studies reported that the decrease in the activity of antioxidants is linked with many diseases that lead to cause of OS [7,[23][24][25][26][27][28]. Thus the decrease in the arylestease activity can contributes in the increasing of MDA.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress and antioxidant agents are involved in pathophysiology, prevention or treatment of various chronic diseases such as cardiovascular diseases (CVDs), obesity, diabetes mellitus and metabolic syndrome (MetS; Liguori et al, 2018;Talebi et al, 2019;Sadeghpour et al, 2020). Furthermore, it has been suggested that dietary intake and food quality are two factors associated with the modulation of oxidative stress.…”
Section: Introductionmentioning
confidence: 99%